2020
DOI: 10.3389/fnins.2020.00841
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Interval Training Decreases Muscle Sympathetic Nerve Activity in Men With Essential Hypertension and in Normotensive Controls

Abstract: Exercise training is a cornerstone in reducing blood pressure (BP) and muscle sympathetic nerve activity (MSNA) in individuals with essential hypertension. Highintensity interval training (HIIT) has been shown to be a time efficient alternative to classical continuous training in lowering BP in essential hypertension, but the effect of HIIT on MSNA levels has never been investigated. Leg MSNA responsiveness to 6 weeks of HIIT was examined in 14 hypertensive men (HYP; age: 62 ± 7 years, night time BP: 136 ± 12/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 62 publications
7
22
0
Order By: Relevance
“…Measurements were made with an isolated tungsten needle inserted into the peroneal nerve, posterior to the fibular head. 11,12 The accessibility of the peroneal nerve was assessed by external stimulation (0–10 mA, 1 Hz, and pulse 0.2 ms) with an isolated stimulator (stimulus isolator, ADInstruments). Upon assessing nerve accessibility, an isolated tungsten electrode (FHC, Bowdoin, ME, United States) was inserted into the peroneal nerve posterior to the fibular head.…”
Section: Methodsmentioning
confidence: 99%
“…Measurements were made with an isolated tungsten needle inserted into the peroneal nerve, posterior to the fibular head. 11,12 The accessibility of the peroneal nerve was assessed by external stimulation (0–10 mA, 1 Hz, and pulse 0.2 ms) with an isolated stimulator (stimulus isolator, ADInstruments). Upon assessing nerve accessibility, an isolated tungsten electrode (FHC, Bowdoin, ME, United States) was inserted into the peroneal nerve posterior to the fibular head.…”
Section: Methodsmentioning
confidence: 99%
“…Perhaps this phenomenon ensures the creation of the most optimal conditions for more intensive blood flow during active muscle work [4]. Most likely, this is a consequence of reduced sympathetic nervous influences that provide basal vascular tone [7,12], and can also be explained by the systematic powerful release of vasodilator metabolites from the hypertrophied skeletal muscles of bodybuilders during regular strength training.…”
Section: Discussionmentioning
confidence: 99%
“…However, compared with other antihypertensive agents, such as diuretics, ACEi, ARB and CCBs, beta-blockers appear to be less protective against stroke and overall mortality, and are more often used as additional drugs for hypertensive patients (74). Exercise is an important way of controlling sympathetic hypertension, and studies have confirmed that high-intensity interval training (e.g., three 60min exercise sessions per week for 4 months) can reduce BP by reducing MSNA (75,76).…”
Section: Sympathetic Dysregulationmentioning
confidence: 99%